Abstracts from the European Respiratory Society Annual Conference 2018 on Thoracic Oncology - Bostantzoglou, Clementine; Iliopoulou, Marianthi; Blum, Torsten Gerriet (Journal of Thoracic Disease; Vol 10, Supplement 25 (September 2018): Journal of Thoracic Disease [Dedicated to the 28th International Congress of the European Respiratory Society (ERS 2018)], 2018)
Lung cancer is the number one cause of death due to cancer worldwide. According to WHO, it accounts for 1.69 million new cases in 2015 (1), whereas in Europe 20.8% of all deaths due to cancer (over 266,000 cases) were attributable to lung cancer in 2011 (2).